Performance Capacity Testing Of Hush Peeling And Soybean Seed Crusing Machine For Home Industry Scale - Pratama, Ravi Putra; Sulaksono, Bambang; Hasan, Husain (Jurnal Teknik Indonesia, 2023)
The process of peeling and splitting soybeans is a process carried out by industry which uses soybeans to clean the skin and at the same time peeling them using a machine that peels the epidermis and also splits the soybeans can speed up the cleaning process. The machine for peeling epidermis and splitting soy beans uses a pulper as the part that peels and splits at the same time in one machine rotation. This model of machine for peeling epidermis and splitting soy beans is intended for home industries with a processing capacity of 10 kg/hour. The performance capacity test was carried out to test the ability to peel and split soybeans using a tube pulper with soybeans that had been soaked in water for 10 hours previously. Based on the tests carried out, it was found that the peeling and splitting capability of the machine for peeling the epidermis and splitting the soybean seeds was produced based on the initial weight before peeling, the soybeans that were completely peeled were 88.2% and the weight of the waste was 11.8%, peeled in imperfect conditions. broken and not peeled based on the influence of the gap in the peeling space of 2mm.